A method for cross-linking aldehyde-chromium composite of vein bridge

Through the aldehyde-chromium composite crosslinking method, the problem of restenosis of venous bridges was solved. The mechanical strength and tolerance of venous bridges were enhanced through the aldehyde-chromium composite crosslinking method, calcification and inflammatory response were reduced, and restenosis of venous bridges was significantly delayed, achieving Effective improvement of the Great Saphenous Vein Bridge.

CN115998955BActive Publication Date: 2024-12-20BEIJING ANZHEN HOSPITAL AFFILIATED TO CAPITAL MEDICAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211580767.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-09
Publication Date
2024-12-20
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

In the prior art, restenosis of venous bridges is serious, especially the poor venous walls and arterial blood flow of the large saphenous vein bridges lead to restenosis, and the existing prevention techniques are not effective.

Method used

By using the aldehyde-chromium composite crosslinking method, the venous bridge is first soaked in a solution containing glutaraldehyde and crosslinked, and then soaked in a solution containing hydroxychromium to crosslink, forming an irreversible covalent chemical bond, enhancing the mechanical strength of the venous bridge and reduce calcification and inflammatory response.

Benefits of technology

It significantly improved the mechanical strength and tolerance of the venous bridge, reduced vascular calcification and inflammatory response, delayed restenosis of the venous bridge, and had no obvious toxic reactions. Both biomechanical tests and animal model experiments showed significant results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115998955B_ABST
    Figure CN115998955B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of vein transplantation, and specifically provides an aldehyde-chromium composite cross-linking method for a vein bridge, comprising the following steps: separating and obtaining the vein bridge, first immersing the vein bridge in a solution containing glutaraldehyde for cross-linking, and then immersing the vein bridge in a solution containing hydroxychromium for cross-linking after cleaning, and obtaining the cross-linked vein bridge after cleaning. The method can not only improve the tolerance of the vein bridge to arterial hypertension and reduce the circumferential ductility of the vein wall; more importantly, it significantly reduces vascular calcification and inflammatory response, reduces tissue immunogenicity, and has no obvious toxic reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of vein transplantation, and in particular to an aldehyde-chromium composite cross-linking method for a vein bridge. Background Art

[0002] At present, the incidence of coronary heart disease ranks second in the spectrum of cardiovascular diseases, with more than 11 million people suffering from the disease and nearly one million deaths each year. Coronary artery bypass grafting (CABG) is one of the most effective treatments for coronary heart disease. As the name suggests, coronary artery bypass grafting is to take the patient's own blood vessels (such as the internal thoracic artery, the great saphenous vein of the lower limbs, etc.) or vascular substitutes to connect the distal end of the stenotic coronary artery with the aorta, allowing blood to bypass the stenotic part and reach the ischemic part, improving myocardial blood supply, and thus achieving the purpose of relieving angina symptoms, improving heart function, improving the quality of life of patients and prolonging life. Among them, the great saphenous vein is the most commonly used graft vessel for coronary artery bypass grafting. However, the restenosis rate of vein grafts after coronary artery bypass grafting is 15% in one year, 30% in five years, and as high as 50% in ten years. There is currently no feasible and effective technology to prevent restenosis of vein grafts. Compared with the internal mammary artery with the best patency rate, the collagen of the adventitia of the great saphenous vein is loose, and the number of smooth muscle cells and elastic fibers in the middle membrane is significantly reduced. The fundamental reason for progressive restenosis of great saphenous vein grafts is the mismatch between the weak vein wall and arterial hemodynamics. At present, the clinical technologies for preventing restenosis of vein grafts mainly include "No-touch" great saphenous vein harvesting technology, great saphenous vein preservation medium technology, and extravascular stent technology. The above technical methods are theoretically feasible, but the practical effects are not ideal and have not been widely used in clinical practice.

[0003] Our laboratory has developed the glutaraldehyde cross-linking technology for the great saphenous vein early on, and studied the biomechanical properties of the great saphenous vein graft adventitia after glutaraldehyde cross-linking. It was found that compared with the control group, glutaraldehyde cross-linking increased the strength of the great saphenous vein wall to a certain extent and reduced its ductility. However, as the research progressed, it was found that the calcification and inflammatory response of the vein graft after glutaraldehyde cross-linking were more serious. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art in that the cross-linked great saphenous vein graft has severe vascular calcification and inflammatory response after treatment, thereby providing an aldehyde-chromium composite cross-linking method for a vein graft.

[0005] The present invention provides an aldehyde-chromium composite cross-linking of a vein bridge, comprising the following steps:

[0006] The vein bridge is first immersed in a solution containing glutaraldehyde for cross-linking, and then immersed in a solution containing hydroxychromium for cross-linking after cleaning, and a cross-linked vein bridge is obtained after cleaning.

[0007] Furthermore, the mass percentage of glutaraldehyde in the solution containing glutaraldehyde is 0.03%-0.9%, preferably 0.3%.

[0008] Furthermore, the mass percentage of chromium hydroxylate in the chromium hydroxylate solution is 0.035%-1.05%, preferably 0.35%.

[0009] Furthermore, the cross-linking time of the vein graft in the solution containing glutaraldehyde is 2-6 minutes, preferably 3 minutes.

[0010] Furthermore, the cross-linking time of the vein bridge in the solution containing chromium hydroxide is 2-6 minutes, preferably 3 minutes.

[0011] During the soaking process, the amino and carbonyl groups in the collagen fibers of the venous bridge adventitia form irreversible covalent chemical bonds with the aldehyde group of glutaraldehyde and the hydroxyl group in hydroxychromium, respectively, and the cross-linking time is the soaking time.

[0012] Furthermore, the chromium hydroxide is prepared by the reaction of basic chromium sulfate and alkali, and the solution containing glutaraldehyde is a physiological saline solution containing glutaraldehyde or an aqueous solution containing glutaraldehyde. Among them, the water of the present invention can be conventional experimental water such as distilled water and purified water. The above-mentioned alkali can be conventional strong alkalis such as sodium hydroxide and potassium hydroxide.

[0013] The chromium hydroxylate solution of the present invention is prepared by conventional methods. For example, the chromium hydroxylate solution used in each embodiment and experimental example is prepared by the following method:

[0014] (1) Take 19 g of sodium dichromate, add 150 ml of distilled water to dissolve, add 48.3 ml of 6 mol / L sulfuric acid (density 1.34 g / ml), and then add 3.26 g of D-Glucose to prepare a solution containing chromium sulfate. The reaction equation is as follows: 4Na 2 Cr 2 O 7 +16H 2 SO 4 +C 6 H 12 O 6 →4Cr 2 (SO 4 ) 3 +4Na 2 SO 4 +6CO 2 ↑+22H 2 O(I).

[0015] (2) Take the chromium sulfate solution obtained in step (1) and add NaHCO 312.18g was added with 262g of distilled water and reacted to obtain Cr(OH)SO 4 The reaction equation is as follows: Cr 2 (SO 4 ) 3 +2NaHCO 3 →2Cr(OH)SO 4 +Na 2 SO 4 +2CO 2 ↑(II).

[0016] (3) Take the Cr(OH)SO 4 100g of the solution was diluted with 5% NaOH solution according to Cr(OH)SO 4 The mass ratio of 1:2 was used for basic titration, and 1.5 ml of 0.1% Triton X-100 was added, and distilled water was added to dilute it, and finally a 1.4% mass fraction of chromium hydroxide (Cr(OH) 3 ) solution, the reaction equation is as follows: Cr(OH)SO 4 +2NaOH→Cr(OH) 3 +Na 2 SO 4 (III).

[0017] (4) 1.4% Cr(OH) 3 The solution is used as the basic application solution, and other concentrations of chromium hydroxide used in the present invention are obtained by diluting the basic application solution with distilled water.

[0018] Furthermore, the vein bridge is a great saphenous vein bridge or a small saphenous vein bridge.

[0019] The venous graft in the present invention can be obtained by conventional methods, for example, conventional open acquisition or minimally invasive acquisition assisted by laparoscope or acquisition by non-contact (ie no-touch) method.

[0020] Further, the venous bridge is collected during coronary artery bypass grafting (CABG) or CABG combined with other cardiac surgeries. Other cardiac surgeries are conventional cardiac surgeries, such as congenital heart surgery, valve surgery, and cardiac and great vessel surgery.

[0021] Furthermore, the fat and fascia surrounding the vein graft were cleared with surgical scissors before immersion.

[0022] Furthermore, one end of the vein graft is ligated before immersion, and the other end is ligated after heparinized blood or saline is injected. The purpose of tension-free filling is to maintain the tubular shape of the vein.

[0023] Furthermore, the cleaning step is to use physiological saline as a cleaning solution for flushing. Preferably, the washing is performed 2-5 times with flowing physiological saline, each time lasting at least 30 seconds (eg, 1 minute, 2 minutes, 3 minutes or 5 minutes).

[0024] The technical solution of the present invention has the following advantages:

[0025] 1. The aldehyde-chromium composite cross-linking method of the vein bridge provided by the present invention comprises the following steps: the vein bridge is first immersed in a solution containing glutaraldehyde for cross-linking, and then immersed in a solution containing hydroxychromium for cross-linking after cleaning, and a cross-linked vein bridge is obtained after cleaning. This method allows the amino group and carbonyl group in the collagen fiber of the outer membrane of the vein bridge to form irreversible covalent chemical bonds with the aldehyde group of glutaraldehyde and the hydroxyl group in the hydroxychromium, respectively, and the loose bundle collagen fiber monomers are polymerized into a dense mesh collagen fiber polymer. This method can not only improve the tolerance of the vein bridge to arterial hypertension and reduce the circumferential extensibility of the vein wall; more importantly, it significantly reduces vascular calcification and inflammatory reactions, reduces tissue immunogenicity, and has no obvious toxic reactions.

[0026] In addition, the results of biomechanical tests and high-pressure expansion experiments showed that this technology significantly increased the mechanical strength of the vein graft and improved the tolerance of the vein graft in the arterial circulation. Animal model experiments showed that the aldehyde-chromium composite cross-linking technology of the outer membrane of the great saphenous vein graft can significantly inhibit the restenosis of the vein graft.

[0027] 2. The aldehyde-chromium composite cross-linking method of the vein bridge provided by the present invention uses specific concentrations of glutaraldehyde and hydroxychromium and controls the specific cross-linking time, specifically by controlling the concentration (mass percentage) of glutaraldehyde in the glutaraldehyde-containing solution to 0.03%-0.9%, especially 0.3%; controlling the concentration (mass percentage) of hydroxychromium in the hydroxychromium-containing solution to 0.035%-1.05%, especially 0.35%. The biomechanical properties of the vein bridge are closer to those of the LIMA bridge, which is currently the best patency bridge material.

[0028] The cross-linking time in the solution containing glutaraldehyde is controlled to be 2-6 minutes, preferably 3 minutes. The cross-linking time in the solution containing chromium hydroxide is controlled to be 2-6 minutes, preferably 3 minutes; better improve the mechanical strength of the vein bridge while reducing its side effects such as inflammation and vascular calcification.

[0029] 3. The aldehyde-chromium composite cross-linking method of the vein bridge provided by the present invention improves the conformation of collagen fibers in the vein wall, enhances the mechanical strength of the vein bridge, and prevents restenosis of the vein bridge. This technology polymerizes the loose bundle-like collagen fiber monomers of the outer membrane into dense mesh-like collagen fiber polymers to play a mechanical support role similar to that of "extravascular stents", while avoiding the implantation of foreign substances, breaking through the current mainstream application of various extravascular stents to prevent restenosis of vein bridges. The research bottleneck is changed from complex to simple, and a new technology is provided for the prevention and treatment of restenosis of vein bridges.

[0030] The technology is simple, cheap, and time-saving. It is not affected by the diameter of the vein bridge and the anastomosis technology, which is conducive to clinical transformation. In addition, the aldehyde-chromium composite cross-linking technology of the vein bridge is an irreversible cross-linking technology, which can permanently improve the spatial conformation of collagen fibers and continuously enhance the mechanical strength of blood vessels, which is conducive to long-term improvement of the pathological reconstruction of the vein bridge, improve the long-term efficacy of coronary artery bypass grafting, reduce the risk of adverse cardiovascular events after coronary artery bypass grafting, and reduce the medical burden of patients. The aldehyde-chromium composite cross-linking technology of the vein bridge can realize the standardization of vein bridge improvement, the cross-linking agent cost is low, and it will not significantly increase medical costs. It is of great significance for clinical transformation and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 are the Von Kossa silver nitrate staining images (×40) and HE staining images (×100) of the great saphenous vein (SV) of the three groups in Experimental Example 1;

[0033] Figure 2 The results of the calcification ratio per unit area and inflammatory cell count of the three groups of SV in Experimental Example 1; where * indicates the comparison between the aldehyde-chromium composite cross-linking group and the control group; # indicates the comparison between the aldehyde-chromium composite cross-linking group and the glutaraldehyde group;

[0034] Figure 3 The Masson staining and membrane thickening results of the three groups of SV in Experimental Example 3; I is the hyperplastic intima; M is the smooth muscle layer (purple), L is the luminal surface of the vascular intima, and the triangle represents the boundary between the intima and the media;

[0035] Figure 4 is the axial mechanical characteristic curve of group A in experimental example 4;

[0036] Figure 5 is the circumferential mechanical characteristic curve of group A in experimental example 4;

[0037] Figure 6 is the axial mechanical characteristic curve of group B in experimental example 4;

[0038] Figure 7 is the circumferential mechanical characteristic curve of group B in experimental example 4;

[0039] Figure 8 Comparison results of axial stress-strain curves between group A and group B;

[0040] Fig. 9 Comparison results of circumferential stress-strain curves between group A and group B. DETAILED DESCRIPTION

[0041] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0042] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0043] Among them, Klein solution contains NaCl 118mmol / L, KCl 4.7mmol / L, CaCl 2 2.5mmol / L,KH 2 PO 4 1.18mmol / L,MgSO 4 0.57mmol / L,NaHCO 3 14.2mmol / L, glucose 5.5mmol / L solution.

[0044] Example 1

[0045] The remaining great saphenous vein (SV) after coronary artery bypass grafting (CABG) surgery was collected, and the fat and fascia around each SV were carefully removed with surgical scissors, and the SV was divided into segments of about 5 cm in length. Among them, the great saphenous vein was obtained by non-contact (i.e. no-touch) method. In this embodiment, the obtained great saphenous vein was subjected to aldehyde-chromium composite cross-linking, which specifically includes the following steps: (1) The proximal end of the SV was ligated with No. 4 silk thread, and the distal end was connected to a syringe and injected with heparinized arterial blood (tension-free filling, only maintaining the tubular shape of the vein), and then ligated with No. 4 silk thread. (2) At room temperature, the SV was first soaked in 100 mL of physiological saline containing 0.3% (mass percentage) glutaraldehyde for 3 minutes, and rinsed with flowing physiological saline 3 times, each time for 1 minute. Then the SV was soaked in 100 ml of a solution containing hydroxychromium for 3 minutes, and rinsed with flowing physiological saline 3 times, each time for 1 minute. The mass fraction of the solution containing hydroxychromium is 0.35%, of which 0.35% Cr(OH) 3 The solution is 1.4% Cr(OH) 3 The solution was diluted 4 times.

[0046] Heparinized arterial blood collection: During CABG surgery, 1 mg / kg (body weight) of unfractionated heparin was injected into the patient's central vein 3 minutes later, and 20 ml of heparinized arterial blood was drawn from the peripheral arterial pressure monitoring line.

[0047] Example 2

[0048] The remaining great saphenous vein (SV) after coronary artery bypass grafting (CABG) surgery was collected, and the fat and fascia around each SV were carefully removed with surgical scissors, and the SV was divided into segments of about 5 cm in length. Among them, the great saphenous vein was obtained by non-contact (i.e. no-touch) method. In this embodiment, the obtained great saphenous vein was subjected to aldehyde-chromium composite cross-linking, specifically (1) the proximal end of the SV was ligated with No. 4 silk thread, and the distal end was connected to a syringe and injected with heparinized arterial blood (tension-free filling, only maintaining the tubular shape of the vein), and then ligated with No. 4 silk thread. (2) At room temperature, the SV was first soaked in 100 mL of physiological saline containing 0.2% (mass percentage) glutaraldehyde for 2 minutes, and rinsed with running physiological saline twice, each time for 2 minutes. Then the SV was soaked in 100 ml of a solution containing hydroxychromium for 4 minutes, and rinsed with running physiological saline 4 times, each time for 30 seconds. The mass fraction of the solution containing hydroxychromium is 0.40%, of which 0.40% Cr(OH) 3 The solution is 1.4% Cr(OH) 3 The solution was diluted 3.5 times. Heparinized arterial blood was the same as in Example 1.

[0049] Example 3

[0050] The remaining great saphenous vein (SV) after coronary artery bypass grafting (CABG) surgery was collected, and the fat and fascia around each SV were carefully removed with surgical scissors, and the pieces were divided into segments of about 5 cm in length. Among them, the great saphenous vein was obtained by non-contact (i.e. no-touch) method. In this embodiment, the obtained great saphenous vein was subjected to aldehyde-chromium composite cross-linking, specifically (1) the proximal end of the SV was ligated with No. 4 silk thread, and the distal end was connected to a syringe and injected with heparinized arterial blood (tension-free filling, only maintaining the tubular shape of the vein), and then ligated with No. 4 silk thread. (2) At room temperature, the SV was first soaked in 100 mL of physiological saline containing 0.5% (mass percentage) glutaraldehyde for 3 minutes, and rinsed with running physiological saline 5 times, each time for 1 minute. Then the SV was soaked in 100 ml of a solution containing hydroxychromium for 2 minutes, and rinsed with running physiological saline twice, each time for 30 seconds. The mass fraction of the solution containing hydroxychromium is 0.30%, of which 0.30% Cr(OH) 3 The solution is 1.4% Cr(OH) 3 The solution was diluted 4.7 times. Heparinized arterial blood was the same as in Example 1.

[0051] Comparative Example 1

[0052] The remaining great saphenous vein (SV) after coronary artery bypass grafting (CABG) surgery was collected, and the fat and fascia around each SV were carefully removed with surgical scissors, and the pieces were divided into segments of about 5 cm in length. Among them, the great saphenous vein was obtained by non-contact (i.e. no-touch) method. In this comparative example, the obtained great saphenous vein was cross-linked with glutaraldehyde, specifically: (1) The proximal end of the SV was ligated with No. 4 silk thread, and the distal end was connected to a syringe to inject heparinized arterial blood (tension-free filling, only maintaining the tubular shape of the vein), and then ligated with No. 4 silk thread. (2) At room temperature, the SV was immersed in 100 mL of normal saline containing 0.3% (mass percentage) glutaraldehyde for outer membrane cross-linking for 6 minutes, and rinsed with running normal saline 3 times, each time for 1 minute.

[0053] Comparative Example 2

[0054] The remaining great saphenous vein (SV) after coronary artery bypass grafting (CABG) surgery was collected, and the fat and fascia around each SV were carefully removed with surgical scissors and divided into segments of approximately 5 cm in length. Among them, the great saphenous vein was obtained by a non-contact (i.e., no-touch) method. In this comparative example, the obtained great saphenous vein was not cross-linked, specifically: (1) The proximal end of the SV was ligated with No. 4 silk thread, and the distal end was connected to a syringe to inject heparinized arterial blood (tension-free filling, only maintaining the tubular shape of the vein), and then ligated with No. 4 silk thread. (2) The SV was soaked in 100 mL of normal saline for 6 minutes at room temperature.

[0055] Experimental Example 1 Vascular calcification detection

[0056] 1. Experimental methods

[0057] (1) The fat and fascia around each SVG were removed with surgical scissors, and the remaining great saphenous vein (SV) after coronary artery bypass grafting (CABG) was collected. The great saphenous vein segments were cut into 5 mm × 5 mm vascular slices and randomly divided into three groups, a control group, a glutaraldehyde group, and an aldehyde-chromium compound group, with 12 slices in each group. The aldehyde-chromium compound group was treated by the method of step (2) of Example 1, the glutaraldehyde group was treated by the method of step (2) of comparative example 1, and the control group was treated by the method of step (2) of comparative example 2. The vascular slices of the three groups were then stored in 50 ml of normal saline containing antibiotics (containing 400 U of penicillin).

[0058] (2) Thirty-six 6-week-old male SD rats were randomly divided into three groups, 12 in each group, control group, glutaraldehyde group, and hydroxychromium group. After intraperitoneal anesthesia with 3% sodium pentobarbital 100ul / 100g, the hair of the 2cm×2cm area on the back of the rats was shaved, and after local disinfection with iodine, a 1cm long skin incision was made with a scalpel, and the subdermal fascia tissue was freed with a vascular clamp to make a subcutaneous pouch of about 1cm×1cm. The vascular slices treated in item (1) above were then embedded in the corresponding groups, and the incisions were finally sutured with 4-0 silk thread. After 4 weeks of feeding, the rats were killed by pulling the neck, and the vascular slices were removed along the original incision. The vascular slices were stained with Von Kossa silver nitrate and HE to observe the calcification and inflammatory cell infiltration of the vascular slices, respectively.

[0059] 2. Experimental results

[0060] Von Kossa silver nitrate staining shows that the brown-red tissue is the deposited calcium salt; HE staining shows that the cell nucleus is stained blue-brown, indicating inflammatory cells. Figure 1 Von Kossa staining showed that patchy calcifications were observed in the venous slices of the control group, spotty calcifications were observed in the glutaraldehyde group, and only scattered spotty calcifications were observed in the aldehyde-chromium compound group. HE staining showed that dense inflammatory cell infiltration was observed in the venous slices of the control group, only scattered inflammatory cells were observed in the aldehyde-chromium compound group, and sparse inflammatory cell infiltration was observed in the glutaraldehyde group. The quantitative results are shown in Tables 1 and Figure 1 shown.

[0061] Table 1 Results of vascular calcification and inflammation

[0062] variable Control group Glutaraldehyde group Aldehyde chromium complex Calcification ratio per unit area (%) 52.7±6.4 14.3±3.1 6.7±1.8*# Inflammatory cell count per unit area (%) 82.7±10.4 48.3±5.8 9.7±1.4*#

[0063] * indicates that the aldehyde-chromium compound group has significant difference compared with the control group, # indicates that the aldehyde-chromium compound group has significant difference compared with the glutaraldehyde group.

[0064] As shown in the table above, 4 weeks after implantation, the calcification degree and inflammatory response of the venous patch in the aldehyde-chromium composite cross-linking group were significantly lower than those in the control group (*P<0.001) and the glutaraldehyde group (#P<0.001). This result shows that the aldehyde-chromium composite cross-linking has the effect of anti-calcification and reducing tissue immunogenicity.

[0065] Experimental Example 2 Toxicity Test

[0066] 1. Experimental Materials

[0067] The great saphenous vein extract was prepared according to the national standard GB / T 16886.12-2005. Specifically, the great saphenous vein samples after cross-linking in Example 1 and Comparative Example 1 were taken, and the sample surface area to extract volume ratio was 3 cm 2 / ml ratio, put the sample in physiological saline and extract at 37℃ for 48 hours. The supernatant is the extract.

[0068] 2. Experimental methods

[0069] (1) Local toxicity: Four 6-week-old SD male rats were randomly divided into two groups, a glutaraldehyde group and an aldehyde-chromium complex group, with two rats in each group. After intraperitoneal anesthesia with 3% sodium pentobarbital 100ul / 100g, the back was shaved to avoid scratching the skin. After cleaning the skin with 75% alcohol, 5 points were selected on one side of the spine with an interval of 2cm. Each point was intradermally injected with 0.1ml of the extract. Similarly, the same volume of normal saline was injected into the symmetrical points on the opposite side as the control group. The reaction of the injection point and surrounding tissues was observed 24h, 48h, and 72h after injection, and quantitative scoring was performed. No reaction was scored as 0 points, erythema was scored as 1 point, edema was scored as 2 points, and necrosis was scored as 3 points.

[0070] (2) Systemic toxicity: 36 6-week-old SD male rats were randomly divided into 3 groups: control group, glutaraldehyde group and aldehyde-chromium complex group, with 12 rats in each group. After intraperitoneal anesthesia with 3% sodium pentobarbital 100ul / 100g, the glutaraldehyde group and aldehyde-chromium complex group were intraperitoneally injected with 2ml of sample extract, while the control group was intraperitoneally injected with 2ml of normal saline. The survival of the rats was observed after injection, and venous blood samples were drawn 1 day, 3 days and 7 days after injection to detect plasma C-reactive protein and IL-6 concentrations, and the average values ​​were calculated.

[0071] 3. Experimental results

[0072] (1) Local toxicity test results

[0073] There was no inflammatory reaction at the injection site in the control group, 3 erythema and 2 blisters in the glutaraldehyde group, and 4 erythema and 1 blister in the aldehyde-chromium composite cross-linking group. There was no necrosis at all injection sites. The specific scoring results are shown in Table 1.

[0074] Table 2 Results of local toxicity reactions

[0075] Grouping Control group Glutaraldehyde group Aldehyde chromium complex P Average skin lesion score 0 0.7 0.6 >0.05

[0076] P>0.05 indicates that there is no statistically significant difference between the glutaraldehyde group and the aldehyde-chromium compound group.

[0077] The differences in the average skin lesion scores between the control group and the two experimental groups were all ≤1.0, indicating that the two experimental groups (glutaraldehyde group and aldehyde-chromium compound group) had no obvious local toxic reactions.

[0078] (2) Systemic toxicity test results

[0079] There was no death in the three groups of rats during the test period. There was no statistical difference in CRP and IL-6 among the three groups. Only the IL-6 level in the glutaraldehyde group was significantly higher than that in the control group (111.63±11.04ng / L vs 95.71±14.40ng / L, P=0.006). There was no statistical difference between the aldehyde-chromium complex group and the control group. The results showed that compared with the control group, the aldehyde-chromium complex cross-linking did not produce obvious systemic toxicity reactions. Compared with the glutaraldehyde group, the aldehyde-chromium complex cross-linking group reduced the systemic toxicity reactions.

[0080] Table 3 Comparison of systemic inflammatory indicators among the three groups of rats.

[0081] variable Control group Glutaraldehyde group Aldehyde chromium complex P-value CRP (ug / L) 1620.88±245.80 1670.20±102.64 1656.45±60.05 P>0.05 IL-6 (ng / L) 95.71±14.40 <![CDATA[111.63±11.04 # ]]> 104.19±20.37 P>0.05

[0082] Note: CRP: C-reactive protein; IL-6: interleukin 6; #: P < 0.05 compared with the control group

[0083] Experimental Example 3

[0084] 1. Experimental Materials

[0085] During CABG surgery, great saphenous vein graft (SVG) segments (about 15 m in length) were collected from 45 patients. SVGs were obtained using the "No-touch" technique. After acquisition, the SV was stored in heparinized saline containing arterial blood. The heparinized saline containing arterial blood was prepared by mixing 200 ml of normal saline, 2500 U of heparin, and 20 ml of arterial blood. The room temperature was 23-26°C. All samples were perfused in vitro within 1 hour after acquisition. Inclusion criteria: (1) Elective surgery; (2) Normal renal function, glomerular filtration rate (CKD-EPI method) > 90 ml / min×1.73 m 2 ; (3) No diabetes, varicose veins of the great saphenous vein, or peripheral vascular disease; (4) No history of hormone drug use within 3 months.

[0086] 2. Experimental methods

[0087] The fat and fascia around each SVG were carefully removed with surgical scissors, and then the SVG of 45 patients was cut into 3 equal lengths. The SVG of each patient was randomly divided into 3 groups: a control group, a glutaraldehyde group, and an aldehyde-chromium compound group, with 45 segments in each group. The aldehyde-chromium compound group was cross-linked using the method of Example 1, the glutaraldehyde group was cross-linked using the method of Comparative Example 1, and the control group was uncross-linked using the method of Comparative Example 2.

[0088] The SVGs treated in the above three groups were connected to the in vitro perfusion system ( Provided by School of Life Sciences, Beijing Institute of Technology), continuous pulsatile perfusion for 7 days. Parameter settings: pulsatile frequency 80 times / min, flow rate 50ml / min, average perfusion pressure 100mmHg, systolic pressure / diastolic pressure 120±5 / 90±5mmHg. The culture container and perfusion system are the same solution medium: RPMI-1640 culture medium containing glutamine 4mmol / L, 30wt% fetal bovine serum, 8wt% 70KD-dextran, 1wt% antibacterial-antifungal solution (penicillin 10000U / ml + streptomycin sulfate 10000ug / ml + amphotericin B 25mg / ml + gentamicin 0.5ug / ml), the solution medium is replaced every 48h. Perfusion environment: ambient temperature 37℃, pH7.4. The entire perfusion operation is controlled by a computer system, and hemodynamic parameters are recorded in real time.

[0089] All SVGs after perfusion were stained with Masson staining, the thickness of the intima and media of SVG was measured, and the intima-media thickening ratio was calculated. The intima-media thickening ratio is the result of dividing the intima thickness by the media thickness. This index indicates the degree of intimal hyperplasia. The larger the ratio, the greater the degree of intimal thickening.

[0090] 3. Experimental results

[0091] Compared with the veins in the control group, the intimal hyperplasia of the veins in the glutaraldehyde group and the aldehyde-chromium compound group was significantly reduced after pulsatile perfusion. Masson staining showed that compared with the thickness of the vein intima in the control group, the thickness of the vein intima in the aldehyde-chromium compound group was significantly lower than that in the control group (36.2±3.6um vs.113.4±14.5um, P<0.05), and the thickness of the vein intima in the aldehyde-chromium compound group was significantly lower than that in the glutaraldehyde group (36.2±3.6um vs.59.7±8.8um, P<0.05). The degree of smooth muscle lesions in the aldehyde-chromium compound veins was also reduced compared with the control group and the glutaraldehyde group. Compared with the control group, the aldehyde-chromium compound cross-linking could significantly reduce the SVG intima-media thickening ratio by up to 4.3 times; compared with the glutaraldehyde group, the aldehyde-chromium compound cross-linking could significantly reduce the SVG intima-media thickening ratio by 1.8 times ( Figure 3 ).

[0092] Experimental Example 4 Biomechanical Test

[0093] 1. Experimental Materials

[0094] During CABG surgery, SVG segments (about 10 cm in length) were collected from 42 patients. Each case was divided into 2 segments on average (autologous control to reduce the influence of individual differences), 1 segment received outer membrane aldehyde-chromium composite cross-linking, that is, treated according to the method of Example 1 (Group A, n = 42). The other segment received outer membrane glutaraldehyde cross-linking, that is, treated according to the method of Comparative Example 1 (Group B, n = 42), and two valid measurement data were retained for each sample.

[0095] 2. Experimental methods

[0096] The biomechanical indicators of the great saphenous vein samples before and after cross-linking were measured using a biomechanical testing platform, and the stress-strain curves were drawn.

[0097] The samples were stored in a frozen environment before the test, so they were taken out and placed in 37°C physiological saline for thawing and warming for 5 minutes before the test began. After the samples regained their elasticity, they were cut into splines of about 14 mm in length and 2 mm in width along the axial direction (the direction of the centerline of the blood vessel) and the circumferential direction with a scalpel. After the cutting was completed, the cut splines were measured with a vernier caliper, and their original length, width, and thickness were recorded. In the actual test, to ensure the accuracy of the measurement, when measuring the width and thickness, 5 positions were selected for each spline for measurement and then the average value was taken. In order to prevent the spline from falling off during the stretching process, the length of the spline clamped by the clamps at each end must be greater than or equal to 2 mm. Therefore, in the post-processing stage, the effective length of the spline is the original length minus the length clamped by the two clamps.

[0098] After the material preparation is completed, the tension sensor in the stretching device is calibrated first, and then the length, width, thickness and other data of the pre-measured spline are entered into the computer software control interface. The surface of the sample strip is marked with waterproof blue dots, and the deformation of the spline is quantified by the change in the distance between the two blue dots during the stretching process. Before each spline is formally stretched, it is pre-stretched 5 times, and the pre-stretch length is 2.5% of the effective length of the spline. The speed of pre-stretching and formal stretching is set to 0.05mm / s. During the stretching, the spline is placed on the test bench in 37℃ physiological saline, and a ruler is placed next to the spline as a reference, which is used to obtain the actual distance between the marking points in the subsequent data processing. During the stretching process, the CCD camera above the test bench will take pictures and samples of the stretching process. At the end of each test, the load data applied to the spline measured by the tension sensor and the photos of the spline during the stretching process are saved.

[0099] 3. Experimental data processing

[0100] A total of 178 great saphenous vein splines were subjected to tensile tests on 42 great saphenous vein specimens, including 91 great saphenous vein splines after aldehyde-chromium composite cross-linking (Group A) and 86 great saphenous vein splines after glutaraldehyde cross-linking (Group B). The test data with surface marking points falling off, blurring, splines falling off the clamp, and incomplete data preservation during the stretching process were eliminated, and 59 reasonable and valid great saphenous vein data in Group A and 47 in Group B were screened out.

[0101] 4. Experimental results

[0102] (1) The statistical data of the test samples are as follows:

[0103]

[0104]

[0105] (2) Comparison of axial stress-strain curves

[0106] Figure 8 The results showed that in the low strain zone (elongation range 1.0-1.4), the stress-strain curves of the two groups were basically consistent, and the average elastic Young's membrane volume of group A and group B were 0.536 and 0.508, respectively, P>0.05; in the high strain zone (elongation range 1.4-1.8), the curve of group A was significantly shifted to the left than that of group B, and the average elastic Young's membrane volume of group A and group B were 12.931 and 8.146, respectively, P<0.05.

[0107] The results showed that the strength of the vein wall tissue after hydroxy-chromium composite cross-linking was significantly greater than that of the great saphenous vein after glutaraldehyde cross-linking, which indicates that hydroxy-chromium composite cross-linking can improve the tolerance of the great saphenous vein bridge to arterial hypertension.

[0108] (3) Comparison of circumferential stress-strain curves

[0109] Fig. 9 The results showed that in the low strain zone (elongation rate range 1.0-1.1), the stress-strain curves of the two groups were basically consistent, and the average elastic Young's membrane volume of group A and group B were 0.374MPa and 0.305MPa, respectively, P>0.05; in the high strain zone (elongation rate range 1.1-1.3), the circumferential extension of the veins was the same, and group A required greater stretching force than group B. The average elastic Young's membrane volume of group A and group B was 18.353MPa and 7.840MPa, respectively, P<0.05.

[0110] The results showed that compared with glutaraldehyde cross-linking, the circumferential extensibility of the vein wall was significantly decreased after hydroxychromium composite cross-linking, which indicates that in the same arterial circulation, hydroxychromium composite cross-linking can reduce the excessive expansion of the great saphenous vein graft, while excessive expansion of the great saphenous vein can lead to endothelial cell detachment and dysfunction, initiating the restenosis process of the great saphenous vein graft.

[0111] Experimental Example 5

[0112] 1. Experimental methods

[0113] The left internal mammary artery is currently the best bridge vessel with the best patency after CABG surgery. The remaining great saphenous vein (SV) and the terminal segment of the internal mammary artery (LIMA) during CABG surgery were collected (the vascular materials were all obtained by no-touch method). The fat and fascia around each SV and LIMA were carefully removed with surgical scissors, and then the vascular samples were stored in 4°C gram solution. The SV was cross-linked in the following manner to obtain 16 groups of cross-linked great saphenous veins. The purpose of this experiment is to investigate the effect of different cross-linking agent concentrations on the tensile properties of the great saphenous vein. The cross-linking method is basically the same as that in Example 1, the only difference is that different concentrations of physiological saline containing glutaraldehyde (hereinafter referred to as GA, the mass percentage of glutaraldehyde is 0.03%, 0.3%, 0.6% and 0.9%) and different concentrations of hydroxychromium solution (hereinafter referred to as Cr, the mass percentage of hydroxychromium is 0.035%, 0.35%, 0.7% and 1.05%, respectively) were used in combination, and the other processes were the same as those in Example 1, and a total of 16 groups of cross-linked great saphenous veins were obtained. The physiological properties of the cross-linked great saphenous vein in each group were compared with those of LIMA.

[0114] Use a scalpel to cut the vein sample vertically axially (in the direction of the long axis of the blood vessel) into a blood vessel ring with a width of about 2 mm. After cutting, use a vernier caliper to measure the blood vessel ring and record its original length, width and thickness. In the actual experiment, to ensure the accuracy of the measurement, when measuring the width and thickness, 5 positions of each blood vessel ring are selected for measurement and the average value is taken. Then hang the blood vessel ring on a hook stretched in the opposite direction. All blood vessel rings are placed at 37°C containing 95% O 2 and 5% CO 2 Uniaxial tensile tests were carried out in Kerri fluid.

[0115] In addition, the internal mammary artery was cut into vascular rings and stretched in the same way as the graft vessel reference group for stretch testing.

[0116] Before each vascular ring is formally stretched, it is pre-stretched five times, with a pre-stretching speed of 0.01 mm / s and a length of 5% of the circumference of the vascular ring. The formal stretching speed is the same as the pre-stretching speed. During the entire stretching process, the digital camera above the test bench will take pictures and samples of the stretching process to record the deformation, and the tension sensor connected to the hook will record and save the load applied to the vascular ring in real time for subsequent biomechanical analysis. Four vascular rings at different locations of each sample are taken for effective stretching.

[0117] 2. Biological Computation

[0118] In actual data processing, it is assumed that the vascular wall tissue material is incompressible and the original length of the vascular strip is L 0 , width W 0 , thickness is T 0 , the length of the strip during the stretching process is L, the width is W, and the thickness is T, then:

[0119] W·T·L=W 0 ·T 0 ·L 0

[0120] ① The elongation (λ) is the ratio of the length of the strip after stretching to its original length, and its mathematical expression is:

[0121] λ=L / L 0

[0122] Stress (σ) is the force exerted by the load (F) on the unit cross-sectional area of ​​the strip during the stretching process. Its mathematical expression is:

[0123]

[0124] ② For each vascular ring, take 100 equally spaced energy intervals between its maximum elastic energy and minimum elastic energy. For the same type of tissue, take the average of its stress and elongation in each energy interval to obtain a set of representative curves of stress-elongation curves. For nonlinear relationships, a modified Mooney–Rivlin strain energy density function is used to describe the stress-strain relationship of vascular wall tissue. Its mathematical expression is:

[0125]

[0126] in,

[0127]

[0128]

[0129]

[0130]

[0131] I 1 is the first invariant of the deformation gradient tensor, J is the Jacobian of the deformation gradient tensor, C 1 , D 1 and D 2 is the empirical material constant, and κ is the Lagrange multiplier of incompressibility. In the uniaxial tensile test of incompressible tissue,

[0132] J=1

[0133] λ 1=λ

[0134]

[0135] ③Young's modulus of elasticity is the slope of each point in the stress-elongation curve, and its mathematical formula is:

[0136]

[0137] ⑤ The breaking strength refers to the load (F) when the vascular ring breaks in the non-hook contact area during the stretching process.

[0138] The above mechanical data were recorded and analyzed using a biomechanical analysis software system, and the stress-strain curves of the vascular samples in different treatment groups were plotted.

[0139] 3. Experimental results

[0140]

[0141] From the meaning of the linear function, we can know that the physical meaning of b is the static contraction force of the vascular wall material, and - indicates that the direction of the force is opposite to the direction of the strain. The physical meaning of a is the Young's modulus of the elasticity of the vascular wall material. In the elongation range [1-1.4], the Young's modulus of the LIMA group (3.631) is similar to that of the 0.3% glutaraldehyde + 0.35% hydroxychromium group (3.189), indicating that the biomechanical properties of the great saphenous vein treated with 0.3% GA + 0.35% Cr composite cross-linking are closest to those of the LIMA bridge, and the LIMA bridge is currently the best vascular bridge material with the best patency rate. Therefore, the composite cross-linking effect of 0.3% glutaraldehyde + 0.35% hydroxychromium is the best.

[0142] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A chromium-aldehyde composite cross-linking method for a vein bridge, characterized in that: The steps include: The vein bridge is first immersed in a solution containing glutaraldehyde for cross-linking for 3 minutes, and then immersed in a solution containing hydroxychromium for cross-linking for 3 minutes after cleaning, and a cross-linked vein bridge is obtained after cleaning; the mass percentage of glutaraldehyde in the solution containing glutaraldehyde is 0.3%, and the mass percentage of hydroxychromium in the solution containing hydroxychromium is 0.35%; the hydroxychromium is obtained by reacting basic chromium sulfate with alkali.

2. The aldehyde-chromium composite cross-linking method for a vein bridge according to claim 1, characterized in that: The solution containing glutaraldehyde is a physiological saline solution containing glutaraldehyde.

3. The aldehyde-chromium composite cross-linking method for vein bridge according to claim 1, characterized in that: The solution containing glutaraldehyde is an aqueous solution containing glutaraldehyde.

4. The aldehyde-chromium composite cross-linking method for a vein bridge according to claim 1 or 2, characterized in that: The vein bridge is a great saphenous vein bridge or a small saphenous vein bridge.

5. The aldehyde-chromium composite cross-linking method for a vein bridge according to claim 1 or 2, characterized in that: The venous bridge is collected during CABG surgery or CABG combined with other cardiac surgeries; and / or, before immersing, the step of removing fat and fascia around the venous bridge with surgical scissors is included; and / or, before immersing, the step of ligating one end of the venous bridge and injecting heparinized blood or saline from the other end and then ligating it is included.

6. The aldehyde-chromium composite cross-linking method for a vein bridge according to claim 1 or 2, characterized in that: The cleaning step is to use physiological saline as the cleaning solution for flushing.

7. The aldehyde-chromium composite cross-linking method for a vein bridge according to claim 6, characterized in that: Rinse with running saline 2-5 times, each time for at least 30 seconds.

8. A cross-linked venous bridge obtained by treatment with the aldehyde-chromium composite cross-linking method for venous bridges according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for modifying tissue material utilized in surgical implantation and modified material

    CN1415383A